UTILISING THE MEDIA GAMBLER TO INCREASE THE MOTIVATION OF ENGLISH LANGUAGE LEARNERS IN CLASS VII.A SMPN 1 BUA , LUWU REGENCY - Daming, Srinanengsi; Yanti, Yuliana Agustina; Tanan, Yuliana; Syam, Ummu Haerah; Ufrawati, Ufrawati (La Ogi : English Language Journal, 2024)
English is one of the compulsory subjects at school. In studying English with the theme "Traveling", some students in Class VIL.A of SMP Negeri 1 Bua, Luwu Regency, found it difficult and really needed suitable media because in this theme one of them was learning how to describe places, in this case tourist attractions. Therefore, to increase students' motivation in studying the theme "Traveling" very interesting media is needed, namely image media. So that the learning and teaching process can run smoothly and achieve maximum results. The purpose of this research is to find out: (1) whether the application of image media can increase motivation to learn English with the theme Traveling in students of Class VII.A of SMP Negeri 1 Bua, Luwu Regency, (2) how image media can be applied to increase motivation to learn language English with the theme "Traveling" for Class VII.A students of SMP Negeri 1 Bua, Luwu Regency. The subjects of this research were Class VII.A students in the odd semester of SMP Negeri 1 Bua, Luwu Regency, academic year 2018/2019. This research is limited to the theme 'Travelling. The research design used is Classroom Action Research (PTK). The learning tools used are the Learning Implementation Plan (RPP), and Student Activity Sheets. Meanwhile, the instrument used in this research was a test sheet on student learning outcomes.From the analysis of research data it can be concluded that: (1) The application of image media can increase motivation to learn English with the theme 'Traveling", readiness to learn, understanding and learning achievement of students in Class VIL.A SMP Negeri 1 Bua Luwu Regency, (2) Enthusiasm , enthusiasm, joy and creativity in the form of student activity during the teaching and learning process has increased, (3) Students' ability to express meaning and describe images has also increased, and (4) The results of assignments and daily tests have increased.